PROCESSING, UTILIZATION AND DISPOSAL OF WASTE IN THE STEEL INDUSTRY IN ISFAHAN, IRAN - J. Nouri; M. Ghanaei; M. Ashtari (Tehran University of Medical Sciences, 1999)
Environmental pollutions are in considerable attention in steel industries in Iran, where mostly are located around Isfahan. Therefore, an investigation was done mainly on the industrial pollution and waste related to the Isfahan Steel Complex. A plant was installed to collect the uncontrolled fumes, gases and particulates from blast furnace number II during tapping. This plant collects about 2 tons of dust each shift which previously were directed into the atmosphere. The efficiency of the system is going to be improved with some correction currently under way. Asbestos was used very widely for different purposes (about 124 tons per year) as powder, sheets, ropes and woven materials. In steel ladles, preheating furnaces of rolling mills and the power generating plant, asbestos is used as a heat insulator. The small amount of asbestos still being used is kept strictly under control and asbestos and waste is disposed of in a suitable manner. Blast furnace slag is used in the cement industry and construction works and in the slag wool plant especially built for this purpose close to the complex. Efforts have been made to replace dangerous solvents like carbon tetrachloride and other hazardous organic solvents with less toxic ones. The environmental management emphasizes the maintenance and repair of electrofilters, venture scrubbers, bag filter houses, mulicyclones and other means of pollution control which almost all are under way. The use of a venture scrubber with and adjustable throat is being considered to enhance the efficiency of the converters. Converter slag and other waste containing chemicals including cyanide ions are the main subjects being examined at present.